The Influence of Attraction, Facility, and Accessibility Performance on Domestic Tourists’ Decision to Visit A Destination - Candra Dewi, Dian (Bulletin of Management and Business, 2024)
The tourism sector plays a strategic role in the national economy, particularly in increasing regional revenue and creating employment opportunities. Domestic tourists’ decision to visit a destination is influenced by several factors, including attraction performance, facilities, and accessibility. This study aims to analyze how these three factors affect tourists' decisions to visit Malang, Batu, and Malang Regency. Using descriptive and verification methods with a quantitative approach, data were collected through surveys of 120 respondents and analyzed using Path Analysis. The results indicate that tourists have a positive perception of attractions, facilities, and accessibility in Malang Raya. However, attraction performance has the most dominant influence on visit decisions, while accessibility still faces challenges such as traffic congestion and limited public transportation. Although facilities are rated positively, their distribution remains uneven, making some secondary destinations less optimal in attracting visitors. These findings highlight the need for more innovative tourism attraction strategies, a more equitable distribution of facilities, and improvements in accessibility, both in infrastructure and information services. By enhancing these three aspects, Malang Raya's tourism competitiveness can be improved, attracting more domestic tourists and contributing more significantly to the regional economy.